Simplified simulation of a small Pelton turbine using OpenFOAM. Issue 1 (June 2021) - Hidalgo, V; Díaz, C; Erazo, J; Simbaña, S; Márquez, D; Puga, D; Velasco, R; Mafla, C; Barragán, G; Parra, C; Valencia, E; Luo, X
Abstract: In Ecuador, the implementation of hydroelectric plants has had remarkable growth in the energy sector due to its high efficiency, low environmental impact and opportunities to generate employment. One of the sectors with the greatest benefits due to this type of energy has been the rural sector, where several small power plants with a generating capacity between 500KW and 1MW have been installed, which are usually Pelton turbines. In the present research it is necessary to use reverse engineering followed by a numerical study to performance of small Pelton turbines due to the fact that geometry dimensions have not been provided. For this purpose, the geometry has been obtained by applying reverse engineering using a technique based on the solidification of polymers. A silicon elastomer is spread over the buckets to obtain a rubber-type shell and it is then cover with plaster to maintain the shape of the rubber. A 3D scanner is used to obtain a cloud of points which is then processed to generate a faceted surface model. The three-dimensional model is edited and improved using CAD software. A basic simulation is presented to show that this reverse engineering process can be used to perform numerical analysis of Pelton turbines.